Rancang Bangun Model Prototipe Media Pembelajaran Mitigasi Bencana Berbasis Augmented Reality Sebagai Sarana Pendidikan Kebencanaan - Aprilla Fortuna; Ikhwan Rahmansyaf; Febri Prasetya; Wahyu Zulya Syaputra; Detty Rahmadhani; Sakinah Saklaili; Muhamad Ikhwan Bagus; Erna Sinu Linda; Welli Andriani; Thariq Muhammad; Alda Deria (Universitas Negeri Padang, 2023)
Indonesia is one of the most disaster-prone countries in the world as evidenced by the World Risk Index 2019 data, Indonesia is ranked 37th out of 180 countries. The younger generation as agents of change must be able to have a positive influence on the community on the importance of preparedness and mitigation as an effort to reduce the impact of disaster risk. This research intends to design the development of Augmented Reality-based disaster mitigation learning media as a means of disaster education. The method used is the development of a prototype model consisting of listen to customer, build/revise mock-up, customer test-drive mock-up. This stage is carried out with the stages of needs analysis, design, testing, implementation, and evaluation. The results showed that the Blackbox Fire Disaster Mitigation-AR test was successfully displayed as expected (valid) with the target user being the community and students, especially early childhood children building creative, critical, and innovative thinking patterns in solving problems about disasters. Novelty given in developing ideas about disaster mitigation educational media in order to realize quality education and handling climate change. It can be concluded that the presence of Augmented Reality-based disaster mitigation learning media is considered very useful in supporting the learning process in the 21st century and making it easier for users to implement the knowledge gained into daily life by knowing the stages before and after disaster mitigation through disaster education.